Effects of mandibular setback with or without maxillary advancement osteotomies on pharyngeal airways: An overview of systematic reviews. - Su Keng Tan; Wai Keung Leung; Alexander Tin Hong Tang; Roger A Zwahlen (PLoS ONE, 2017)
Mandibular setback osteotomies potentially lead to narrowing of the pharyngeal airways, subsequently resulting in post-surgical obstructive sleep apnea (OSA).To summarize current evidence from systematic reviews that has evaluated pharyngeal airway changes after mandibular setback with or without concomitant upper jaw osteotomies.PubMed, EMBASE, Web of Science, and Cochrane Library databases were searched with no restriction of language or date. Systematic reviews studying changes in pharyngeal airway dimensions and respiratory parameters after mandibular setback with or without concomitant upper jaw osteotomies have been identified, screened for eligibility, included and analyzed in this study.Six systematic reviews have been included. While isolated mandibular setback osteotomies result in reduced oropharyngeal airway dimensions, the reduction is lesser in cases with concomitant upper jaw osteotomies. Only scarce evidence exists currently to what happens to naso- and hypo-pharyngeal airways. There is no evidence for post-surgical OSA, even though some studies reported reduced respiratory parameters after single-jaw mandibular setback with or without concomitant upper jaw osteotomies.Although mandibular setback osteotomies reduce pharyngeal airway dimensions, evidence confirming post-surgical OSA was not found. Nevertheless, potential post-surgical OSA should be taken into serious consideration during the treatment planning of particular orthognathic cases. As moderate evidence exists that double-jaw surgeries lead to less compromised post-surgical pharyngeal airways, they should be considered as the method of choice especially in cases with severe dentoskeletal Class III deformity.PROSPERO (registration number: CRD42016046484).